The Effectiveness of the Academic Program “A-I-U-E-O Vocal Adventure” as an Innovation in Oral Language Learning on the Vocal Production Skills of Students with Hearing Impairments at SLB PGRI KAMAL - Watini; Yasmin Firdausi; Khofidotur Rofiah (GRAB KIDS: Journal of Special Education Need, 2026)
Oral language development, particularly vowel production, is a fundamental component of early communication and poses challenges for students with hearing impairments due to limited auditory input. Students with mild hearing impairment retain residual hearing that can be optimized through structured and multisensory instructional approaches. This study aimed to examine the effectiveness of the Academic Program of Vocal Sound Adventure A–I–U–E–O in improving vowel production skills in a student with mild hearing impairment at SLB PGRI Kamal. A Single Subject Research (SSR) method with an A–B design was employed, consisting of a baseline phase and an intervention phase. The participant was a second-grade student with mild hearing impairment and typical cognitive functioning. Data were collected through structured vowel production assessments and systematic observations of learning behaviors, focusing on sound perception, articulation, vocal clarity, and learning engagement. The findings demonstrated a clear improvement in vowel production abilities following the intervention, indicated by a stable baseline, a marked level change, and a consistent upward trend during the intervention phase. These results suggest that multisensory oral language instruction through the Vocal Sound Adventure A–I–U–E–O program is effective in supporting vowel production development in students with mild hearing impairment, despite limitations related to the single-subject design.